The woman warrior : memoirs of a girlhood among ghosts - Kingston, Maxine Hong (Knopf : distributed by Random House, 1976)
In her award-winning book The Woman Warrior, Maxine Hong Kingston created an entirely new form<U+2014>an exhilarating blend of autobiography and mythology, of world and self, of hot rage and cool analysis. First published in 1976, it has become a classic in its innovative portrayal of multiple and intersecting identities<U+2014>immigrant, female, Chinese, American. As a girl, Kingston lives in two confounding worlds: the California to which her parents have immigrated and the China of her mother<U+2019>s “talk stories.” The fierce and wily women warriors of her mother<U+2019>s tales clash jarringly with the harsh reality of female oppression out of which they come. Kingston<U+2019>s sense of self emerges in the mystifying gaps in these stories, which she learns to fill with stories of her own. A warrior of words, she forges fractured myths and memories into an incandescent whole, achieving a new understanding of her family<U+2019>s past and her own present.